Imaging in mice and men: Pathophysiological insights into multiple sclerosis from conventional and advanced MRI techniques. (November 2019) - Krämer, Julia; Brück, Wolfgang; Zipp, Frauke; Cerina, Manuela; Groppa, Sergiu; Meuth, Sven G.
Highlights: This review summarizes MRI and histopathological studies in mice and humans with MS. Hereby it partially elucidates the underlying pathophysiology behind imaging findings. It recommends imaging protocols for the future examination of different aspects of MS. Further in vivo imaging and histopathological studies in MS mouse models are necessary. A combination of imaging techniques is necessary to examine the pathophysiology of MS. Abstract: Magnetic resonance imaging (MRI) is the most important tool for diagnosing multiple sclerosis (MS). However, MRI is still unable to precisely quantify the specific pathophysiological processes that underlie imaging findings in MS. Because autopsy and biopsy samples of MS patients are rare and biased towards a chronic burnt-out end or fulminant acute early stage, the only available methods to identify human disease pathology are to apply MRI techniques in combination with subsequent histopathological examination to small animal models of MS and to transfer these insights to MS patients. This review summarizes the existing combined imaging and histopathological studies performed in MS mouse models and humans with MS ( in vivo and ex vivo ), to promote a better understanding of the pathophysiology that underlies conventional MRI, diffusion tensor and magnetization transfer imaging findings in MS patients. Moreover, it provides a critical view on imaging capabilities and results in MS patients and mouse models and for future studies recommends how to combine those particular MR sequences and parameters whose underlying pathophysiological basis could be partly clarified. Further combined longitudinal in vivo imaging and histopathological studies on rationally selected, appropriate mouse models are required.